Perspektif Hipersemiotika pada Pertunjukan Sori in the Land of Lembuna Karya Flying Balloons Puppet dan Gwen Knox - Alma'ieda Alma'ieda; I Nyoman Murtana (Gondang: Jurnal Seni dan Budaya, 2021)
Sori in the Land of Lembuna Performance by Flying Balloons Puppet and Gwen Knox presenting a discourse of river habitat polution phenomenon packed as explorative and imaginative. Analytical method done with hypersemiotic perspective which qualitative interpretative. The review on signs that were present in the performance is done with hypersemiotic perspective. Hypersemiotic perspective analysis used are content of recycled signs that were present in the performance. Lembuna is a character representing the myth of Lembudana and Lembudini, as a past reality, recontextualized into present reality in the form of a Plastic Monster as a representative of environmental pollution from plastic wastes piling up in the river ecosystem. The present of both merge into new reality in the form of a performance, so between signs and reality, even reality and non reality are hard to be distinguished.